Terahertz Physics / [electronic resource] - Lewis, R. A. (Cambridge : Cambridge University Press, 2013)
Terahertz physics covers one of the least explored but richest regions of the electromagnetic spectrum. Designed for independent learning, this is the first book to open up this exciting new field to students of science and engineering. Written in a clear and consistent style, the textbook focuses on an understanding of fundamental physical principles at terahertz frequencies and their applications. Part I outlines the foundations of terahertz science, starting with the mathematical representation of oscillations before exploring terahertz-frequency light, terahertz phenomena in matter and the terahertz interactions between light and matter. Part II covers components of terahertz technology, from sources of terahertz frequency radiation, through the manipulation of the radiation, to its detection. Part III deals with applications, including time-domain spectroscopy. Highlighting modern developments and concepts, the book is ideal for self-study. It features precise definitions, clear explanations, instructive illustrations, fully worked examples, numerous exercises and a comprehensive glossary.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Submillimeter waves; Electromagnetic waves; Physics; Terahertz spectroscopy